The impact of time-integrated active or passive sampling methods on bioanalytical water quality risk assessment - Ron van der Oost; Jaap Postma; Willie van den Berg; Mai Thao Nguyen; Insam al Saify; Corine J. Houtman; Harrie Besselink; Evert-Jan van den Brandhof; Abraham Brouwer (Journal of Water Process Engineering, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Validation of MEWS, NEWS, NEWS-2 and qSOFA for different infection foci at the emergency department, the acutelines cohort - Carolina Hincapié-Osorno; Raymond J. van Wijk; Douwe F. Postma; Jacqueline Koeze; Jan C. Ter Maaten; Fabian Jaimes; Hjalmar R. Bouma (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Sepsis is a leading cause of morbidity and mortality globally. The lack of specific prognostic markers necessitates tools for early risk identification in patients with suspected infections in emergency department (ED). This study evaluates the prognostic accuracy of various Early Warning Scores (EWS)—MEWS, NEWS, NEWS-2, and qSOFA—for in-hospital mortality, 30-day mortality, and ICU admission, considering the site of infection. Methods A retrospective analysis was conducted using data from the Acutelines cohort, which included data collected from patients admitted to the University Medical Centre Groningen ED between September 2020 and July 2023. Patients were included if they had an ICD-10 code for infection. EWS were calculated using clinical data within 8 h post-admission. Predictive performance was assessed using AUC-ROC, calibration by the Hosmer-Lemeshow test and calibration curves, and operative characteristics like sensitivity and specificity. Results A total of 1661 patients were analyzed, with infections distributed as follows: lower respiratory tract (32.9%), urinary tract (30.7%), abdominal (12.5%), skin and soft tissue (9.5%), and others (8.2%). The overall in-hospital mortality was 6.7%, and ICU admission was 7.1%. The highest AUC-ROC for in-hospital mortality prediction was observed with NEWS and NEWS-2 in abdominal infections (0.86), while the lowest was for qSOFA in skin and soft tissue infections (0.57). Predictive performance varied by infection site. Conclusions The study highlights the variability in EWS performance based on infection site, emphasizing the need to consider the source of infection in EWS development for sepsis prognosis. Tailored or hybrid models may enhance predictive accuracy, balancing simplicity and specificity.

Resilience and vulnerability: perspectives of key informants on the uncertain future of Pacific salmon in British Columbia - Hannah G. Postma; Yovela Wang; Valerie Berseth; Nathan Young; Steven J. Cooke; Scott G. Hinch (Regional Environmental Change, 2024)

Effects of different soil organic amendments (OAs) on extracellular polymeric substances (EPS) - Yujia Luo; Juan Bautista Gonzalez Lopez; H. Pieter J. van Veelen; Dirk-Jan Daniel Kok; Romke Postma; Dirk Thijssen; Valentina Sechi; Annemiek ter Heijne; T. Martijn Bezemer; Cees J.N. Buisman (European Journal of Soil Biology, 2024)

Experimental quantification of genetic and ontogenetic effects on fighting behavior in the broad-horned flour beetle - Toshiki Nishitani; Kentarou Matsumura; Erik Postma; Manmohan Dev Sharma; David J Hosken; Takahisa Miyatake (Behavioral Ecology and Sociobiology, 2024)
Most animal behaviors show large within- and among-individual variation, and this includes competitive male behaviors. With male fighting for example, aggressiveness often correlates with dominance, and contest duration varies with age. However, few studies have directly quantified how mean aggressiveness and contest duration, the variation among individuals in both traits, and the relationship among them, vary with age. Here we address these gaps and examine the effect of male age and genotype on two key aspects of male fighting behavior - aggressiveness (here measured as latency to fight) and contest duration - and the relationship between them. We do this using isogenic lines of the broad-horned flour beetle Gnatocerus cornutus . We observed fighting behavior of paired males of similar body size and age. Using uni- and multivariate mixed models, we show that although there was a significant difference between younger and older males in contest duration, mean aggressiveness was not affected by male age. However, the variation in aggression and fight duration varied with age, being greater in younger and older males respectively. Additionally, although there was a positive correlation between aggressiveness and contest duration in younger males, this relationship was not found in older males. Finally, the only significant genetic effect was for aggression in younger males. Our study shows that age differentially shapes key components of male fighting behavior as well as the relationship among them, highlighting the dynamic nature and context-dependence of fighting.

Innovating transcriptomics for practitioners in freshwater fish management and conservation: best practices across diverse resource-sector users - C. A. D. Semeniuk; K. M. Jeffries; T. Li; C. M. Bettles; S. J. Cooke; B. A. Dufour; E. A. Halfyard; J. W. Heath; K. Keeshig; N. E. Mandrak; A. J. Muir; L. Postma; et al. (Reviews in Fish Biology and Fisheries, 2022)

Therapeutic treatment of dietary docosahexaenoic acid for particle-induced pulmonary inflammation in Balb/c mice - Paige Fletcher; Raymond F. Hamilton; Joseph F. Rhoderick; Britten Postma; Mary Buford; James J. Pestka; Andrij Holian (Inflammation Research, 2021)

Imaging the role of blood–brain barrier disruption in normal cognitive ageing - Inge C. M. Verheggen; Joost J. A. de Jong; Martin P. J. van Boxtel; Alida A. Postma; Jacobus F. A. Jansen; Frans R. J. Verhey; Walter H. Backes (GeroScience, 2020)
To investigate whether blood–brain barrier (BBB) disruption is a potential mechanism of usual age-related cognitive decline, we conducted dynamic contrast–enhanced (DCE) MRI to measure BBB leakage in a healthy sample, and investigated the association with longitudinal cognitive decline. In a sample of neurologically and cognitively healthy, older individuals, BBB leakage rate in the white and grey matter and hippocampus was measured using DCE MRI with pharmacokinetic modelling. Regression analysis was performed to investigate whether the leakage rate was associated with decline in cognitive performance (memory encoding, memory retrieval, executive functioning and processing speed) over 12 years. White and grey matter BBB leakages were significantly associated with decline in memory retrieval. No significant relations were found between hippocampal BBB leakage and cognitive performance. BBB disruption already being associated with usual cognitive ageing, supports that this neurovascular alteration is a possible explanation for the cognitive decline inherent to the ageing process. More insight into BBB leakage during the normal ageing process could improve estimation and interpretation of leakage rate in pathological conditions. The current results might also stimulate the search for strategies to maintain BBB integrity and help increase the proportion people experiencing successful ageing. Netherlands Trial Register number: NL6358, date of registration: 2017-03-24.

Increase in blood–brain barrier leakage in healthy, older adults - Inge C. M. Verheggen; Joost J. A. de Jong; Martin P. J. van Boxtel; Ed H. B. M. Gronenschild; Walter M. Palm; Alida A. Postma; Jacobus F. A. Jansen; Frans R. J. Verhey; Walter H. Backes (GeroScience, 2020)
Blood–brain barrier (BBB) breakdown can disrupt nutrient supply and waste removal, which affects neuronal functioning. Currently, dynamic contrast-enhanced (DCE) MRI is the preferred in-vivo method to quantify BBB leakage. Dedicated DCE MRI studies in normal aging individuals are lacking, which could hamper value estimation and interpretation of leakage rate in pathological conditions. Therefore, we applied DCE MRI to investigate the association between BBB disruption and age in a healthy sample. Fifty-seven cognitively and neurologically healthy, middle-aged to older participants (mean age: 66 years, range: 47–91 years) underwent MRI, including DCE MRI with intravenous injection of a gadolinium-based contrast agent. Pharmacokinetic modeling was applied to contrast concentration time-curves to estimate BBB leakage rate in each voxel. Subsequently, leakage rate was calculated in the white and gray matter, and primary (basic sensory and motor functions), secondary (association areas), and tertiary (higher-order cognition) brain regions. A difference in vulnerability to deterioration was expected between these regions, with especially tertiary regions being affected by age. Higher BBB leakage rate was significantly associated with older age in the white and gray matter, and also in tertiary, but not in primary or secondary brain regions. Even in healthy individuals, BBB disruption was stronger in older persons, which suggests BBB disruption is a normal physiologically aging phenomenon. Age-related increase in BBB disruption occurred especially in brain regions most vulnerable to age-related deterioration, which may indicate that BBB disruption is an underlying mechanism of normal age-related decline. Netherlands Trial Register number: NL6358, date of registration: 2017-03-24.

Solubility Constraints on Aquatic Ecotoxicity Testing of Anionic Surfactants - J. Hammer; A. M. Tukker; J. F. Postma; J. J. -H. Haftka; J. L. M. Hermens; P. de Voogt; M. H. S. Kraak (Bulletin of Environmental Contamination and Toxicology, 2018)

Biorefinery of the macroalgae Ulva lactuca: extraction of proteins and carbohydrates by mild disintegration - P. R. Postma; O. Cerezo-Chinarro; R. J. Akkerman; G. Olivieri; R. H. Wijffels; W. A. Brandenburg; M. H. M. Eppink (Journal of Applied Phycology, 2018)

Frames of reference and categorical/coordinate spatial relations in a “what was where” task - Francesco Ruotolo; Tina Iachini; Gennaro Ruggiero; Ineke J. M. van der Ham; Albert Postma (Experimental Brain Research, 2016)

The microcyclic conidial stage of Coniochaeta pulveracea and its effect on selected biological interactions - Andrea van Heerden; Marnel Mouton; Ferdinand Postma; Pieter W. J. van Wyk; Barbra Lerm; Willem H. Van Zyl; Cornelius J. Borstlap; Alfred Botha (Folia Microbiologica, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Shared and distinct anatomical correlates of semantic and phonemic fluency revealed by lesion-symptom mapping in patients with ischemic stroke - J. Matthijs Biesbroek; Martine J. E. van Zandvoort; L. Jaap Kappelle; Birgitta K. Velthuis; Geert Jan Biessels; Albert Postma (Brain Structure and Function, 2016)

First confirmed record of a leucistic Antarctic fur seal pup born outside the Scotia Arc Islands - M. Wege; M. Postma; C. A. Tosh; P. J. N. de Bruyn; M. N. Bester (Polar Biology, 2015)

Enhancement of MHC-I Antigen Presentation via Architectural Control of pH-Responsive, Endosomolytic Polymer Nanoparticles - John T. Wilson; Almar Postma; Salka Keller; Anthony J. Convertine; Graeme Moad; Ezio Rizzardo; Laurence Meagher; John Chiefari; Patrick S. Stayton (The AAPS Journal, 2015)

Objective allergy markers and risk of cancer mortality and hospitalization in a large population-based cohort - Niloofar Taghizadeh; Judith M. Vonk; Jeannette J. Hospers; Dirkje S. Postma; Elisabeth G. E. de Vries; Jan P. Schouten; H. Marike Boezen (Cancer Causes & Control, 2015)

Modelling root–soil interactions using three–dimensional models of root growth, architecture and function - Vanessa M. Dunbabin; Johannes A. Postma; Andrea Schnepf; Loïc Pagès; Mathieu Javaux; Lianhai Wu; Daniel Leitner; Ying L. Chen; Zed Rengel; Art J. Diggle (Plant and Soil, 2013)

Modelling root plasticity and response of narrow-leafed lupin to heterogeneous phosphorus supply - Ying L. Chen; Vanessa M. Dunbabin; Johannes A. Postma; Art J. Diggle; Kadambot H. M. Siddique; Zed Rengel (Plant and Soil, 2013)

Age-related reproductive variation in a wild marine mammal population - Martin Postma; Marthán N. Bester; P. J. Nico de Bruyn (Polar Biology, 2013)

The role of Streptococcus pneumoniae in community-acquired pneumonia among adults in Europe: a meta-analysis - M. H. Rozenbaum; P. Pechlivanoglou; T. S. Werf; J. R. Lo-Ten-Foe; M. J. Postma; E. Hak (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD - Nadia N. Hansel; Ingo Ruczinski; Nicholas Rafaels; Don D. Sin; Denise Daley; Alla Malinina; Lili Huang; Andrew Sandford; Tanda Murray; Yoonhee Kim; Candelaria Vergara; Susan R. Heckbert; et al. (Human Genetics, 2013)

Spatiotemporal segregation among summer stocks of beluga (Delphinapterus leucas) despite nuclear gene flow: implication for the endangered belugas in eastern Hudson Bay (Canada) - Julie Turgeon; Pierre Duchesne; Gabriel J. Colbeck; Lianne D. Postma; Mike O. Hammill (Conservation Genetics, 2012)

Phenotypic variability and modelling of root structure of wild Lupinus angustifolius genotypes - Ying Long Chen; Vanessa M. Dunbabin; Johannes A. Postma; Art J. Diggle; Jairo A. Palta; Jonathan P. Lynch; Kadambot H. M. Siddique; Zed Rengel (Plant and Soil, 2011)

Frames of reference and categorical and coordinate spatial relations: a hierarchical organisation - Francesco Ruotolo; Tina Iachini; Albert Postma; Ineke J. M. van der Ham (Experimental Brain Research, 2011)

Prevalence of antibodies against Ascaris suum and its association with allergic manifestations in 4-year-old children in the Netherlands: the PIAMA birth cohort study - E. Pinelli; S. M. Willers; D. Hoek; H. A. Smit; L. M. Kortbeek; M. Hoekstra; J. Jongste; F. Knapen; D. Postma; M. Kerkhof; R. Aalberse; J. W. B. Giessen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

NETMORPH: A Framework for the Stochastic Generation of Large Scale Neuronal Networks With Realistic Neuron Morphologies - Randal A. Koene; Betty Tijms; Peter van Hees; Frank Postma; Alexander de Ridder; Ger J. A. Ramakers; Jaap van Pelt; Arjen van Ooyen (Neuroinformatics, 2009)

Spared unconscious influences of spatial memory in diencephalic amnesia - Albert Postma; Rémy Antonides; Arie J. Wester; Roy P. C. Kessels (Experimental Brain Research, 2008)

Differential effects of non-informative vision and visual interference on haptic spatial processing - Robert Volcic; Joram J. van Rheede; Albert Postma; Astrid M. L. Kappers (Experimental Brain Research, 2008)

Multisensory integration affects ERP components elicited by exogenous cues - Valerio Santangelo; Rob H. J. Van der Lubbe; Marta Olivetti Belardinelli; Albert Postma (Experimental Brain Research, 2008)

Ammonium Toxicity at High pH in a Marine Bioassay Using Corophium volutator - Belinda J. Kater; Marco Dubbeldam; Jaap F. Postma (Archives of Environmental Contamination and Toxicology, 2006)

Spatial attention triggered by unimodal, crossmodal, and bimodal exogenous cues: a comparison of reflexive orienting mechanisms - Valerio Santangelo; Rob H. J. Van der Lubbe; Marta Olivetti Belardinelli; Albert Postma (Experimental Brain Research, 2006)

The effect of neuronal morphology and membrane-permeant weak acid and base on the dissipation of depolarization-induced pH gradients in snail neurons - A. Pantazis; P. Keegan; M. Postma; C. J. Schwiening (Pflügers Archiv - European Journal of Physiology, 2006)

Effect of above‐ground plant species on soil microbial community structure and its impact on suppression of Rhizoctonia solani AG3 - P. Garbeva; J. Postma; J. A. Van Veen; J. D. Van Elsas (Environmental Microbiology, 2006)
Summary The extent of soil microbial diversity is seen to be critical to the maintenance of soil health and quality. Different agricultural practices are able to affect soil microbial diversity and thus the level of suppressiveness of plant diseases. In a 4‐year field experiment, we investigated the microbial diversity of soil under different agricultural regimes. We studied permanent grassland, grassland turned into arable land, long‐term arable land and arable land turned into grassland. The diversity of microbial communities was described by using cultivation‐based and cultivation‐independent methods. Both types of methods revealed differences in the diversities of soil microbial communities between different treatments. The treatments with higher above‐ground biodiversity generally maintained higher levels of microbial diversity. Moreover, a positive correlation between suppression of Rhizoctonia solani AG3 and microbial diversity was observed. Permanent (species‐rich) grassland and grassland turned into maize stimulated higher microbial diversities and higher levels of suppressiveness of R. solani AG3 compared with the long‐term arable land. Effects of agricultural practices on Bacillus and Pseudomonas communities were also observed and clear correlations between the levels of suppressiveness and the diversities of these bacterial groups were found. This study highlighted the importance of agricultural management regime for soil microbial community structure and diversity as well as the level of soil suppressiveness.

Interruption from irrelevant auditory and visual onsets even when attention is in a focused state - Rob H. J. van der Lubbe; Albert Postma (Experimental Brain Research, 2005)

Within-trophic group interactions of bacterivorous nematode species and their effects on the bacterial community and nitrogen mineralization - M. B. Postma-Blaauw; F. T. de Vries; R. G. M. de Goede; J. Bloem; J. H. Faber; L. Brussaard (Oecologia, 2005)

Diel vertical migration of major fish-species in Lake Victoria, East Africa - Kees Goudswaard; Jan H. Wanink; Frans Witte; Egid F.B. Katunzi; Michiel R. Berger; David J. Postma (Hydrobiologia, 2004)

Diffusion of new medicines into hospital practice - J. E. F. Zwart-van Rijkom; N. S. Breekveldt-Postma; H.G.M. Leufkens; A. C. G. Egberts (European Journal of Clinical Pharmacology, 2003)

Delay improves performance on a haptic spatial matching task - Sander Zuidhoek; Astrid M. L. Kappers; Rob H. J. van der Lubbe; Albert Postma (Experimental Brain Research, 2003)

Developmental regulation and downstream effects of the knox class homeobox genes Oskn2 and Oskn3 from rice - A. Dorien Postma-Haarsma; Saskia Rueb; Enrico Scarpella; Willem den Besten; J. Harry C. Hoge; Annemarie H. Meijer (Plant Molecular Biology, 2002)

Morphological Deformities in Chironomus Riparius Meigen Larvae after Exposure to Cadmium over Several Generations - L. Janssens de Bisthoven; J. Postma; A. Vermeulen; G. Goemans; F. Ollevier (Water, Air, & Soil Pollution, 2001)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Fluctuating Life-History Parameters Indicating Temporal Variability in Metal Adaptation in Riverine Chironomids - D. Groenendijk; B. van Opzeeland; L. M. Dionisio Pires; J. F. Postma (Archives of Environmental Contamination and Toxicology, 1999)

Characterization of the KNOX class homeobox genes Oskn2 and Oskn3 identified in a collection of cDNA libraries covering the early stages of rice embryogenesis - A. Dorien Postma-Haarsma; Ira I.G.S. Verwoert; Oscar P. Stronk; Jan Koster; Gerda E.M. Lamers; J. Harry C. Hoge; Annemarie H. Meijer (Plant Molecular Biology, 1999)

Alterations in life-history traits of Chironomus riparius (diptera) obtained from metal contaminated rivers - J. F. Postma; A. van Kleunen; W. Admiraal (Archives of Environmental Contamination and Toxicology, 1995)

Control and regulation of metabolic fluxes in microbes by substrates and enzymes - K. van Dam; N. Jansen; P. Postma; P. Richard; G. Ruijter; M. Rutgers; H. P. Smits; B. Teusink; J. van der Vlag; M. Walsh; H. V. Westerhoff (Antonie van Leeuwenhoek, 1993)

Energetics of glucose uptake in a Salmonella typhimurium mutant containing uncoupled enzyme IIGlc - G. J. G. Ruijter; P. W. Postma; K. van Dam (Archives of Microbiology, 1991)

Quantitative aspects of glucose metabolism by Escherichia coli B/r, grown in the presence of pyrroloquinoline quinone - R. W. J. Hommes; J. A. Simons; J. L. Snoep; P. W. Postma; D. W. Tempest; O. M. Neijssel (Antonie van Leeuwenhoek, 1991)

Physiological significance and bioenergetic aspects of glucose dehydrogenase - Oense M. Neijssel; Ronald W. J. Hommes; Pieter W. Postma; David W. Tempest (Antonie van Leeuwenhoek, 1989)

The influence of the culture pH value on the direct glucose oxidative pathway in Klebsiella pneumoniae NCTC 418 - R. W. J. Hommes; P. W. Postma; D. W. Tempest; O. M. Neijssel (Archives of Microbiology, 1989)

The separate roles of PQQ and apo-enzyme syntheses in the regulation of glucose dehydrogenase activity in Klebsiella pneumoniae NCTC 418 - R. W. J. Hommes; P. T. D. Herman; P. W. Postma; D. W. Tempest; O. M. Neijssel (Archives of Microbiology, 1989)

The functional significance of glucose dehydrogenase in Klebsiella aerogenes - R. W. J. Hommes; B. van Hell; P. W. Postma; O. M. Neijssel; D. W. Tempest (Archives of Microbiology, 1985)

Virulence ofEscherichia coli strains isolated from urine of patients with acute cystitis and from faeces of healthy women - J. F. van den Bosch; P. Postma; D. van Brenk; P. A. M. Guinée; J. de Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1981)

Regulation of sugar transport in Salmonella typhimurium - P. W. Postma; B. J. Scholte (Antonie van Leeuwenhoek, 1981)

Virulence of Escherichia coli in acute pyelonephritis, acute cystitis and asymptomatic bacteriuria - J. F. van den Bosch; P. L. Oe; P. Postma; J. de Graaff; D. M. MacLaren; W. H. Jansen; P. A. M. Guinée (Antonie van Leeuwenhoek, 1980)

Hemolysis and urinary virulence of Escherichia coli. - J. F. Bosch; P. Postma; J. Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1980)

Urinary virulence of E. coli in experimental haematogenous pyelonephritis - J. F. van den Bosch; P. Postma; J. de Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1979)